Anticancer effects of 6-diazo-5-oxo-L-norleucine (DON)-loaded PLGA nanoparticles in triple-negative breast cancer by inhibiting glutamine metabolism: An integrated bioinformatic and experimental approach - Tatar, Cansu; Erdemir, Aysegul (ELSEVIER, 2025)
Triple-negative breast cancer (TNBC) remains a medical problem for which no targeted therapy has been developed because no Achilles heel feature has been identified. In this study, we sought to elucidate the dependence on glutamine metabolism in TNBC by bioinformatics analysis, identify relevant genes, synthesize 6-diazo-5-oxo-L-norleucine (DON)-loaded PLGA nanoparticles, and evaluate their anticancer effects targeting the glutamine pathway in vitro. The GEO2R tool was utilized to examine the GSE10843, GSE57083, GSE34211, GSE26370, and GSE263696 datasets and identify differentially expressed genes (DEGs). Pathway enrichment analyses were performed utilizing KEGG, Enrichr, and STRING tools. Gene expression in UALCAN and survival analysis were performed with Kaplan-Meier Plotter. Bioinformatic results revealed that glutamine metabolism is a notable metabolic target in TNBC. DON, the glutamine antagonist selected to inhibit glutamine metabolism, has failed in clinical studies due to systemic toxicity and inadequate specificity. DON-NPs were synthesized to overcome these challenges using the W/O/W double-emulsion solvent evaporation technique. Physicochemical characterization was conducted by ZetaSizer and FT-IR analysis, and cytotoxicity was assessed in MDA-MB-231 cells. The expression of GLS, ASST, SCD, and RPS6KA2 genes detected in bioinformatic analyses was confirmed by qRT-PCR. The size of DON-NPs was measured at 176.7 +/- 4.53 nm, with a zeta potential of-40.9 +/- 2.78 mV and a PDI value of 0.242 +/- 0.01. The IC50 values of DON-NPs and DON were determined at 1.9 mu g/mL and 4 mu g/mL, respectively. DON-NPs exhibited greater anti-proliferative and apoptotic effects than DON, along with reduced GLS expression and enzyme activity. Our results demonstrate that DON-NPs for glutamine-dependent TNBC enhanced anticancer effects in vitro.
Keywords: Triple-negative breast cancer; Nanoparticle; Bioinformatics; Glutamine addiction; 6-diazo-5-oxo-L-norleucine (DON); Anti-tumor activity; AMINO-ACID; PHASE-I; DELIVERY; DRUG; CYTOTOXICITY; EXPRESSION; SURVIVAL; TARGETS; GROWTH; CELLS; Pharmacology & Pharmacy